Analysis of the Symbolic Meaning of Traditional Jamu Packages at Nguter According to Semiotics Charles Sanders Peirce - Andriyana, Nova (Universitas Ahmad Dahlan, 2024)
Jamu made from processed herbal plants has become an alternative treatment option for the Javanese people to prevent and alleviate disease symptoms. Attractive packaging of herbal products can create a positive visual impression, encouraging consumers to try them. This study examines eight jamu packages incorporating elements of Javanese culture, interpreting the meanings they convey. Examples of the analyzed names include Sri Putih, Sari Asih, Sari Asmara, Arum Bulan, Candra Dewi, Sepet Wangi, Super Semar Turmeric Powder, and Candik Ayu. The article also investigates the context behind the use of icons, symbols, and indexes on the packaging. The names of the jamu packages are derived from the Bausastra dictionary, considering the basic meanings used in naming these products. Ultimately, the study concludes that jamu packaging carries symbolic meanings based on Charles Sanders Peirce’s semiotic method, which suggests to potential consumers the benefits of the products. These symbolic meanings can influence consumers through the icons, symbols, and indices on the packaging.